Chylomicrons promote intestinal absorption and systemic dissemination of dietary antigen (ovalbumin) in mice. - Yuehui Wang; Sarbani Ghoshal; Martin Ward; Willem de Villiers; Jerold Woodward; Erik Eckhardt (PLoS ONE)
Background A small fraction of dietary protein survives enzymatic degradation and is absorbed in potentially antigenic form. This can trigger inflammatory responses in patients with celiac disease or food allergies, but typically induces systemic immunological tolerance (oral tolerance). At present it is not clear how dietary antigens are absorbed. Most food staples, including those with common antigens such as peanuts, eggs, and milk, contain long-chain triglycerides (LCT), which stimulate mesenteric lymph flux and postprandial transport of chylomicrons through mesenteric lymph nodes (MLN) and blood. Most dietary antigens, like ovalbumin (OVA), are emulsifiers, predicting affinity for chylomicrons. We hypothesized that chylomicron formation promotes intestinal absorption and systemic dissemination of dietary antigens. Methodology/principal findings Absorption of OVA into MLN and blood was significantly enhanced when OVA was gavaged into fasted mice together with LCT compared with medium-chain triglycerides (MCT), which do not stimulate chylomicron formation. The effect of LCT was blocked by the addition of an inhibitor of chylomicron secretion, Pluronic L-81. Adoptively transferred OVA-specific DO11.10 T-cells proliferated more extensively in peripheral lymph nodes when OVA was gavaged with LCT than with MCT or LCT plus Pluronic L-81, suggesting that dietary OVA is systemically disseminated. Most dietary OVA in plasma was associated with chylomicrons, suggesting that these particles mediate systemic antigen dissemination. Intestinal-epithelial CaCo-2 cells secreted more cell-associated, exogenous OVA when stimulated with oleic-acid than with butyric acid, and the secreted OVA appeared to be associated with chylomicrons. Conclusions/significance Postprandial chylomicron formation profoundly affects absorption and systemic dissemination of dietary antigens. The fat content of a meal may affect immune responses to dietary antigens by modulating antigen absorption and transport.